Bromide as the Directing Group for β-Arylation of Thiophenes - Wang, Cai-Xia; Sheng, Fei-Fei; Liu, Kai-Hui; Gu, Jian-Guo; Shen, Kang; Sun, Zheng-Yi; Hong, Kunlun; Zhang, Hong-Hai (Synthesis, 2022)
Direct β-arylation of thiophene derivatives with bromide as directing group is disclosed. The reaction is conducted with PdCl2/(p-tolyl)3P as catalyst, silver carbonate as additive, and aryl iodide as coupling partner, affording brominated biaryl compounds as product. Control experiments indicated that the presence of bromide group enhances the reactivity of the C–H bond, enabling β-arylation. Furthermore, the C–Br bond can be easily converted into many useful functional groups through a wide range of methodologies. The mechanistic study suggests that silver salt plays a key role in the C–H bond-activation step.
Keywords: β-arylation; bromide; thiophene; silver